2021
DOI: 10.1111/all.14783
|View full text |Cite
|
Sign up to set email alerts
|

Association between ambient air pollution and development and persistence of atopic and non‐atopic eczema in a cohort of adults

Abstract: Background: There is limited information on risk factors for eczema in adults. Recent evidence suggests that air pollution may be associated with increased incidence of eczema in adults. We aimed to assess this possible association.Methods: Ambient air pollution exposures (distance from a major road, nitrogen dioxide [NO 2 ], fine particulate matter with an aerodynamic diameter ≤2.5 µm [PM 2.5 ])were assessed for the residential address of Tasmanian Longitudinal Health Study participants at ages 43 and 53 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 38 publications
0
18
1
Order By: Relevance
“…In an in vivo study evaluating the effects of 2 ppm NO 2 exposure on human nasal epithelium by electron microscopy, the luminal margin membranes of ciliary cells were ultrastructurally altered in six of seven nasal epithelial samples after NO 2 exposure. 314,315 Ozone gas has a variable lifetime and occurs both in the upper and lower atmospheres, almost at ground level. Ground-level O 3 is the main component of photochemical smog and is formed in the presence of sunlight by chemical reactions between oxides of nitrogen and volatile organic compounds emitted by motor vehicles, power plants, industrial boilers, refineries, and chemical plants.…”
Section: Environmental Subs Tan Ce S Affec Ting the Epithelial Barrier Smentioning
confidence: 99%
See 1 more Smart Citation
“…In an in vivo study evaluating the effects of 2 ppm NO 2 exposure on human nasal epithelium by electron microscopy, the luminal margin membranes of ciliary cells were ultrastructurally altered in six of seven nasal epithelial samples after NO 2 exposure. 314,315 Ozone gas has a variable lifetime and occurs both in the upper and lower atmospheres, almost at ground level. Ground-level O 3 is the main component of photochemical smog and is formed in the presence of sunlight by chemical reactions between oxides of nitrogen and volatile organic compounds emitted by motor vehicles, power plants, industrial boilers, refineries, and chemical plants.…”
Section: Environmental Subs Tan Ce S Affec Ting the Epithelial Barrier Smentioning
confidence: 99%
“…NO 2 can cause epithelial barrier dysfunction in the upper as well as the lower airways. In an in vivo study evaluating the effects of 2 ppm NO 2 exposure on human nasal epithelium by electron microscopy, the luminal margin membranes of ciliary cells were ultrastructurally altered in six of seven nasal epithelial samples after NO 2 exposure 314,315 …”
Section: Environmental Substances Affecting the Epithelial Barriersmentioning
confidence: 99%
“…The sum of external factors that an individual is exposed to throughout life is referred to as the exposome 41,42 . The combination of multiple factors, such as cigarette smoke, air pollutants, chemicals, aeroallergens, and diet, contributes to the development and exacerbation of asthma and other allergic diseases 1,43‐47 …”
Section: Introductionmentioning
confidence: 99%
“…Particulate matter 2.5 (PM 2.5 ), the main component of DEP, exacerbated AR through TJ disruption in a mouse model of allergic rhinitis 51,52 . A population‐based prospective study has shown that a 2.3 parts per billion increase in nitrogen dioxide (NO 2 ) is associated with an increased risk of prevalent and atopic eczema in male adults 47 . Exposure to traffic‐related air pollutants, PM 2.5 , PM 10 , and oxides of nitrogen, is associated with increased odds of incident eczema, particularly PM 2.5 , and is more pronounced with nonatopic eczema in elderly women 53 .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Schnass et al conducted a cohort study and concluded that tra c-related air pollution would increase the prevalence of eczema for elder (Schnass et al, 2018). However, Lopez et al found that long-term air pollution has no adverse effect on adult eczema (Lopez et al, 2021). The same dispute can also be found in AR's research.…”
Section: Introductionmentioning
confidence: 97%